School‐related pressure and parental support as predictors of change in student stress levels from early to middle adolescence. (13th January 2021) - Kulakow, Stefan; Raufelder, Diana; Hoferichter, Frances
ABSTRACT: Introduction: One major stressor of adolescents relates to the pressure students perceive from their parents accompanied by high academic expectations, while in contrast parental support is related to low levels of stress. However, it is not clear whether the perceived parental pressure and support contribute to a change in students' stress level from early to middle adolescence and if there are differences among students from low vs. high track schools. Methods: Thus, based on the conservation of resources theory, this two‐wave study examined the role of perceived maternal and paternal pressure and support for students' general stress level from grades 8 to 9 among students attending high‐ and low‐track schools by applying multigroup multilevel latent change modeling based on data from 1088 8 th grade students ( M Age = 13.70, SD = 0.53, 53.9% girls at Time 1). Results: Results indicate that the general stress level from early to middle adolescence increases for students from low‐track schools only. This change increases even more if students from lowtrack schools perceive pressure from their fathers, whereas perceived paternal support dampen the increase of stress. For students from high‐track schools, perceived maternal pressure is positively and maternal support negatively related to students' stress level in grade 8. Overall, boys tend to report lower stress levels compared to girls. Conclusions: The findings of the present study support the conservation of resources theory, as both perceived support and pressure from parents and the educational context predict students' stress development during adolescence. Highlights: This study expands the sparse research on school‐related parental pressure and support. Stress levels from 8th‐9th grade increase for students from low‐track schools only. Perceived paternal support minimizes low‐track students' stress. Perceived paternal pressure contributes to high stress levels of low‐track students. Maternal support and pressure play a key role for high‐track students' stress.